Application of Combined SWOT and AHP for Strategy Development: A Case of Slow Fashion Brand in Bandung, Indonesia - Aldilax, Dandy; Pfoertsch, Waldemar (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2020)
Abstract. Raising global awareness in a sustainable environment intrigued many young designers and environmental activists to create environmentally friendly products. Slow fashion is a new solution to overcome issues caused by fast fashion, which promotes concern about the environment and sustainability of the products proven by materials, process, and disposal of the products. However, there is lack of empirical evidence about strategy development for Slow Fashion brand in Indonesia. This study aims to identify an appropriate strategy for slow fashion brand in Bandung, Indonesia. Bandung is one of the most creative cities in Indonesia, according to UNESCO, and be the main area of the research. Based on the result, researcher can determine several strategies for slow fashion brand in Indonesia. This research used quantitative approach through questionnaire filled during Forum Group Discussion (FGD). In developing the strategies, internal and external factors were carried out from environment scanning and discussion, then analyzed use hybrid methodology of SWOT-AHP. The result of the study concludes four strategies by considering both internal and external factors overall priority score. This study is important in understanding the most important factors to consider in developing strategies to grow a slow fashion brand in Indonesia. Keywords: Analytical Hierarchy Process , Slow Fashion, Strategic Planning , SWOT